Model of Middle Sector of Central Mall, New York World's Fair 1939 (Curt Teich & Co.)
This picture shows the middle sector of the Central mall of the New York World's Fair, a 2,000-foot esplanade lined with 250 trees and hundreds of benches arranged alongside five lagoons. The latter form setting for groups of sculptured symbolic figures, the huge portrait statue of George Washington at his inauguration, the largest Sun Dial in the world, and, at top the Perisphere, largest ball ever constructed by mankind, and the Trylon, a 65-story triangular shaft. About 25 of the largest exhibit buildings face upon the tree-lined area.